2010
DOI: 10.4314/ajtcam.v6i4.57181
|View full text |Cite
|
Sign up to set email alerts
|

Treating gynaecological disorders with traditional Chinese medicine: a review

Abstract: Traditional Chinese Medicine (TCM) has significant advantages in treating gynaecological disorders. The paper has provided a brief introduction on the current progress of treating some gynaecological disorders including endometriosis, infertility, dysmenorrhea, abnormal uterine bleeding, premenstrual syndrome, menopausal syndrome, uterine fibroids, chronic pelvic inflammation, polycystic ovarian syndrome (PCOS), cervicitis and vaginitis with Chinese Herbal Medicine (CHM) and acupuncture. The use of TCM in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 65 publications
6
76
0
Order By: Relevance
“…Accordingly, this preliminary experiment was suspended at our clinic. Several studies attempted to improve blood flow in the body, including that in the ovary, using herbal medicine [15,16], LLLT [18,33] or acupuncture [19]. Iwahata et al [33] reported a significantly higher pregnancy rate with ICSI-LLLT than ICSI alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, this preliminary experiment was suspended at our clinic. Several studies attempted to improve blood flow in the body, including that in the ovary, using herbal medicine [15,16], LLLT [18,33] or acupuncture [19]. Iwahata et al [33] reported a significantly higher pregnancy rate with ICSI-LLLT than ICSI alone.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies attempted to improve oocyte quality and ovum function by adjuncts to assisted reproductive technology (ART), such as dehydroepiandrosterone [13,14] or herbal medicine [15][16][17] administration, low reactive-level laser therapy (LLLT) [18], or acupuncture [19]. Reportedly [15,17,20,21], successful pregnancies were achieved after herbal medicine intake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First-line therapy for PCOS is oral contraceptives, which can effectively alleviate hirsutism and acne; however, these may adversely affect glucose tolerance, coagulability, and fertility (Lanham et al, 2006). Acupuncture has been used to treat gynecological disorders for thousands of years (Zhou and Qu, 2009). It is sometimes chosen by women with PCOS as an alternative therapy or used as an adjunct while undergoing infertility treatment (Stener-Victorin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis with the symptoms of progressive dysmenorrhea, chronic pelvic pain, deep dyspareunia, infertility, menstrual abnormalities, and aggravated pelvic can seriously affect the physical and mental health of patients (Liu and Lang, 2011;Sun et al, 2011;Zhou and Qu, 2009;Zhou et al, 2012). It is a common gynecological disease and recently its occurrence rate is increasing (Sun et al, 2011;Zhou and Qu, 2009).…”
Section: Introductionmentioning
confidence: 99%